Atividade anti-Candida in vitro dos inibidores seletivos da recaptação da serotonina frente às cepas resistentes ao fluconazol e sua atividade em isolados formadores de biofilme - Silva, Rose Anny Costa (2016)
It is known that candidiasis has been the most documented disease in different groups of patients with immunodeficiency, among all the opportunistic fungal infections diseases. Oftentimes, these infections are related to a biofilm formation, that can be originated from implanted biomaterials or reveal on the host surface. However, antifungal drugs available on the market are restricted and limited to a low number compared to antibacterial drugs. Adding this fact to the increase resistance of the genre Candida regarding the main treatment today, fluconazole, the need for a research on new therapeutic strategies is evident, from the learning of other molecules to non-classic use of already available medicine. Recent researches have revealed a wide antifungal activity of selective serotonin reuptake inhibitor (SSRIs), classic antidepressants. Aware of this context, the main goal is to evaluate antifungal potential of fluoxetine, sertraline, and paroxetine facing Candida spp. planktonic cells resistant to fluconazole, as well as its action mechanism and the viability of biofilms treated with fluoxetine. The evaluation of the antifungal effect on the SSRIs on 13 strains of Candida spp. was determined using broth microdilution technique (M27-A3). A sensibility evaluation of Candida spp. fungal biofilm within 24h of fluoxetine was made the colorimetric assay with the tetrazolium salt (MTT) assay in 96-well plates, defining then, the viability of sessile cells after treatment. By means of flow cytometry and comet assay analysis, damages on membrane, mitochondria and DNA, that contributed to the elucidation of the probable action mechanism of SSRIs on C. albicans representative strains were studied. All strains of Candida spp. resistant to fluconazole showed, after 24h, Minimum Inhibitory Concentration (MIC), which varied between 20 – 160 μg/mL for fluoxetine, 10 – 20 μg/mL for sertraline, and 10 – 100,8 μg/mL for paroxetine, concluding then, that all of them present antifungal activity within the tested range. According the data found, the SSRIs cause fungal death after plasmatic membrane and mitochondrial damages, which activate apoptotic-signalling pathways, resulting loss of cellular viability on dose-dependent form in each one of the tested drugs. Regarding the isolated biofilm formers, Candida parapsilosis presented MIC of approximately 40 μg/mL, C. albicans with 80 μg/mL, C. tropicalis and C. glabrata with 160 μg/mL when exposed to fluoxetine, this reduction was considered statistically significant at the cellular activity of the biofilm (P < 0.05). Therefore, it is concluded that SSRIs are capable of inhibit the growth in vitro of Candida spp.., both in planktonic form, as biofilm, inducing cellular death by apoptosis, this set of data acknowledge the great importance of antidepressant options for patients that compose risk groups for fungal infections.